Viroid pathogenesis: a critical appraisal of the role of RNA silencing in triggering the initial molecular lesion - Flores, Ricardo; Navarro, Beatriz; Delgado, Sonia; Serra, Pedro; Di Serio, Francesco (FEMS microbiology reviews, 2020)
ABSTRACT The initial molecular lesions through which viroids, satellite RNAs and viruses trigger signal cascades resulting in plant diseases are hotly debated. Since viroids are circular non-protein-coding RNAs of ∼250–430 nucleotides, they appear very convenient to address this issue. Viroids are targeted by their host RNA silencing defense, generating viroid-derived small RNAs (vd-sRNAs) that are presumed to direct Argonaute (AGO) proteins to inactivate messenger RNAs, thus initiating disease. Here, we review the existing evidence. Viroid-induced symptoms reveal a distinction. Those attributed to vd-sRNAs from potato spindle tuber viroid and members of the family Pospiviroidae (replicating in the nucleus) are late, non-specific and systemic. In contrast, those attributed to vd-sRNAs from peach latent mosaic viroid (PLMVd) and other members of the family Avsunviroidae (replicating in plastids) are early, specific and local. Remarkably, leaf sectors expressing different PLMVd-induced chloroses accumulate viroid variants with specific pathogenic determinants. Some vd-sRNAs containing such determinant guide AGO1-mediated cleavage of mRNAs that code for proteins regulating chloroplast biogenesis/development. Therefore, the initial lesions and the expected phenotypes are connected by short signal cascades, hence supporting a cause-effect relationship. Intriguingly, one virus satellite RNA initiates disease through a similar mechanism, whereas in the Pospiviroidae and in plant viruses the situation remains uncertain. Comparison of symptoms and molecular pathways supports that viroids replicating in chloroplasts initiate disease (specific plant chloroses) by RNA silencing mRNAs encoding proteins involved in chloroplast biogenesis/development, while the situation is unclear for those replicating in nuclei (inducing non-specific alterations like stunting).